SENYAWA BARU PASCA KEBAKARAN PENYEBAB RAPUHNYA BETON BERTULANG - Lukman, Lukman (METANA, 2007)
Abstract Fire can be happened everywhere at anytime, including to building which use reinforced concrete construction. As consequense of the fire. a heating and cooling cycle by turns happen which cause complex fisis and chemical phase chenge. Considering that concrete has teracity againts high temperature without having chemical compound coposition change because of the high  silica, which is until 1000  EC of  temperature   Keyword The  concrete after fire